SISTEM INFORMASI REGISTRASI KAPAL TANGKAP IKAN PADA DINAS KELAUTAN DAN PERIKANAN NTT - Bauana, Candra Ardian Yuventus (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2022)
At the Marine Service of East Nusa Tenggara Province, the information system on Classification in the Office of the Marine Service can be said to be not optimal because there are still many applications of the classification system that are still not perfect, namely by grouping fishing vessels. Meanwhile, in terms of time, search for classification files such as types of ships. fishing vessels are still not in accordance with what is needed and also in classifying vessels according to the weight of the vessel and also the standardization of the vessel and its feasibility. So with that, the author wants to provide a solution for the East Nusa Tenggara provincial marine service office in the form of designing a web-based classification information system for fishing vessels. to be able to overcome problems in the form of grouping types of fishing vessels, and also in applying standardization of a ship based on its weight. The benefit of the application of information technology in the classification of types of fishing vessels is that it can group each type of fishing vessel based on standardization, feasibility and weight so that it is easily found and can more easily obtain clear information. The information system that will be made temporarily can be applied to the East Nusa Tenggara Provincial Marine Service.